Tingkat Keberhasilan Inseminasi Buatan (IB) Berdasarkan Service Per Conception Sapi Limousin Di Kecamatan Pekalongan Kabupaten Lampung Timur - Ardi Wibowo; Novi Eka wati; Kunaifi Wicaksana (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
This research aims to knowing how the success rate of IB limousine cattle based on S/C in Pekalongan District, East Lampung Regency and knowing the factors that influence the success of IB based on S/C in Pekalongan District, East Lampung Regency. The method in this study is a survey method and data obtained by census, all Limousin Cattle that received IB services by the inseminator were used as samples. The success rate of IB limousine cattle in Pekalongan District, East Lampung Regency seen from the S/C in Limousine cattle was included in the normal range of 1.64. The factors that influence the S/C value in Limousine cattle are the BCS score has a positive association with S/C with a value of 0.364, age at first mated has a positive association with S/C with a value of 1.82, the age of the parent is negatively associated with S/C with a value of 1.82 (-0.215) and the shape of the cage wall was negatively associated with S/C with a value of (-0.0643).